2003
DOI: 10.1071/ea02001
|View full text |Cite
|
Sign up to set email alerts
|

Dry matter yield, forage quality and persistence of tall fescue (Festuca arundinacea) cultivars compared with perennial ryegrass (Lolium perenne) in a subtropical environment

Abstract: Abstract. The dry matter (DM) yield, plant persistence and forage quality of tall fescue (Festuca arundinacea) and perennial ryegrass (Lolium perenne) were compared in the subtropical environment of southern Queensland, Australia. The field study was conducted under irrigation with pure, nitrogen fertilised stands of 10 commercial tall fescue cultivars (Advance, AU Triumph, Bombina, Cajun, Dovey, Maximise, Midwin, Torpedo, Quantum and Vulcan), 3 experimental cultivars (ITF 97010, ITF 97020 and PWF 29) and Dobs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
2
14
1
1
Order By: Relevance
“…Similar opportunities have been identified in sub‐tropical Australia (e.g. Lowe and Bowlder, 1995; Callow et al ., 2003). It is necessary to establish, however, that there are no penalties in milk production associated with the use of swards with alternative species before they can be considered for inclusion in dairy cow systems.…”
Section: Discussionsupporting
confidence: 70%
“…Similar opportunities have been identified in sub‐tropical Australia (e.g. Lowe and Bowlder, 1995; Callow et al ., 2003). It is necessary to establish, however, that there are no penalties in milk production associated with the use of swards with alternative species before they can be considered for inclusion in dairy cow systems.…”
Section: Discussionsupporting
confidence: 70%
“…The NDF content of leaf tissue, which is the more preferred forage fraction by animals, was similar for all residual treatments, despite the fact that the leaf NDF content was slightly greater for tall fescue than perennial ryegrass, as expected from previous studies conducted at the sward level (Callow et al, ; Cullen, Bullen, Hutcheson, Jacobs, & Deighton, ; Lowe, Bowdler, Casey, & Moss, ). Also the decrease in leaf blade DMD was related to decreases in leaf tissue NDFD (Table ), as documented previously in other studies (Insua et al, ; Nave, Sulc, & Barker, ).…”
Section: Discussionsupporting
confidence: 79%
“…The nutritive value of forage grasses, including perennial ryegrass and tall fescue‐grazed pasture, has been described extensively in terms of the neutral detergent fibre (NDF) and dry matter digestibility (DMD) at the whole‐sward level (Callow, Lowe, Bowdler, Lowe, & Gobius, ; Fulkerson et al, ; Scheneiter, Camarasa, Carrete, & Amendola, ). However, the dynamic pattern of the nutritive value of the herbage grown during vegetative regrowth is driven primarily by the continuous turnover of successively produced leaves, all of which have different ages and lengths (Chapman, Lee, & Waghorn, ; Insua et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found that tall fescue has lower herbage quality compared to species such as perennial ryegrass and prairie grass (Callow et al, 2003;Sinclair et al, 2006). Th e lower digestibility of tall fescue is largely due to the lower proportion of cell content and lower cell wall digestibility than other species such as perennial ryegrass (Wilman et al, 1996).…”
Section: Discussionmentioning
confidence: 94%
“…Th ere is limited information on the eff ect of leaf stage based defoliation management on the regrowth of tall fescue. To date, studies have investigated the regrowth of tall fescue following defoliation at various heights (Booysen and Nelson, 1975;Virkajarvi, 2003) and current defoliation interval recommendations are based on a combination of number of days and pasture sward surface height (Milne and Johnson, 1997;Callow et al, 2003;Kemp, 2004).…”
mentioning
confidence: 99%